Water-related mutual funds: investment performance and social role. Issue 3 (3rd August 2015) - Alvarez, Marta; Rodríguez, Javier
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the performance and diversification value of water-related funds. As pollution, climate change and accelerated population growth threaten water resources worldwide, such resources have become a sought-after asset. For most investors, it is impractical to physically hold water as part of a portfolio; therefore, an open question is how to better gain exposure to this asset. The authors propose a look at water-related mutual funds, an issue not found addressed in the literature. In addition to the investment potential of these funds, investors might be drawn to them as part of a more comprehensive socially responsible agenda. Design/methodology/approach – In the present study, the authors identify and measure the risk-adjusted performance and diversification value of open-end funds dedicated to investments in water-related securities. Jensen's alpha is used to measure risk-adjusted performance, whereas diversification value is examined by implementing a methodology widely used in the mutual fund literature. Findings – Consistent with previous studies on the performance of ethical or socially responsible mutual funds, the authors found that their sample of water-related mutual funds neither outperform nor underperform two benchmarks. However, the authors also found that they offer potential diversification gains for international mutual funds' portfolios. Research limitations/implications – Open-end water-related mutual funds have only been recently created, and currently, very few funds are available to investors. These facts limit the sample size and the length of the return series examined. Originality/value – The authors have not found a paper that examines the performance and diversification value of water-related mutual funds. These funds present themselves as a practical way for individual investors to gain exposure to the commodity of water.